The impact of shift work and sleep deficiency on health - Agnieszka Możdżyńska; Laura Wojtala; Weronika Pawlak; Weronika Pawłocik; Lena Musiał; Julia Szymańska; Ewa Grabowska; Kamil Kapłon; Anna Rymarz; Dominika Kojder (Kazimierz Wielki University, 2023)
Shift work refers to work that takes place at different hours, including at night. It is estimated that 15% to 20% of the working population works in shift work, particularly in the healthcare, energy, communication systems, public safety, and hospitality industries. Research indicates that shift work, particularly night work, can lead to health problems such as fatigue, exposure to harmful work environments, increased risk of workplace accidents, and sleep disorders. Night work is also associated with increased risk of hypertension, nervous system dysfunction, cardiovascular dysfunction. Those working at night are also more prone to hormonal disorders, digestive disorders, lowered immunity, and cancer. Sleep-wake cycle disorders, such as excessive sleepiness during waking hours and insomnia at night, are symptoms of shift work intolerance syndrome, which can occur after several months or years of shift work. It is estimated that over 20% of shift workers suffer from sleep-wake cycle disorders, and various factors such as chronotype, age, gender, family and social obligations, medications, medical and psychiatric conditions, and shift work experience can impact tolerance of shift work. The treatment of sleep and wake disorders related to shift work includes planning for main sleep and supplementary naps, appropriate exposure to light, treatment with melatonin, taking sleeping and psychostimulant medications.